2014
DOI: 10.1007/s40030-014-0069-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Erosion Prone Areas by Morphometric Analysis Using GIS

Abstract: This study was undertaken to determine the priority watersheds for conservation of natural resources of the Haharo sub catchment in the Damodar catchment of upper Damodar valley area having an area of 565 km 2 involving four watersheds in Jharkhand State in eastern India by morphometric analysis using topographical maps on a scale of 1:50,000. To define the morphometric features of the watershed, the topographic information of the study area at 1:50,000 scaled are taken for analysis with the help of GIS tools.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Therefore, the consequences of these climate and land use changes are essential to quantify the soil erosion rate for sustainable agricultural and environmental development. In India, almost 167 Mha of the area is found vulnerable to water and wind erosion (Das, 2014). Food and Agriculture Organization (FAO) reported that 25 to 40 billion tons of topsoil are degraded every year and it eventually impact the crop yield and soil properties (Montanarella et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the consequences of these climate and land use changes are essential to quantify the soil erosion rate for sustainable agricultural and environmental development. In India, almost 167 Mha of the area is found vulnerable to water and wind erosion (Das, 2014). Food and Agriculture Organization (FAO) reported that 25 to 40 billion tons of topsoil are degraded every year and it eventually impact the crop yield and soil properties (Montanarella et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested different thematic maps integrated with morphometric variables to determine the suitable areas for citing water and soil conservation measures. In India, several studies on watershed prioritization have been performed based on morphometric analysis using the potential of RS and GIS techniques [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The average value of the bifurcation ratio (Rb) can be determined by determining the average value of the bifurcation ratio (Rb) for a given channel network. According to Table 2 the calculated values for the studied watersheds are 1.95 and 2.45 for SRTM and ATER, accordingly has a similarity with (D. Das, 2014). These values are most common in locations where geologic structure has little effect on drainage patterns.…”
Section: Bifurcation Ratio (Rb) Of Watershedsmentioning
confidence: 63%